Cathelicidin modulates synthesis of Toll-like Receptors (TLRs) 4 and 9 in colonic epithelium - Marin, Maia Solange (2017)
Cathelicidin are innate antimicrobial peptides with broad immunomodulatory functions; however, their role in regulating intestinal defenses is not well characterized. This study aimed to investigate the role of cathelicidin modulating expression of Toll-like receptors (TLRs) 4 and 9 in colonic epithelium in response to bacterial patterns. We demonstrated herein that intestinal epithelial cells, when primed by bacterial lipopolysaccharide (LPS), responded to cathelicidin by increased transcription and protein synthesis of TLR4. This cathelicidin-induced response required the interaction of LPS-TLR4 and activation of MAPK signalling pathways. However, cathelicidin blocked TLR9 responses induced by TLR9 ligand CpG oligodeoxynucleotide (CpG ODN) in these colonic epithelial cells. Modulations of TLRs triggered by cathelicidin in intestinal epithelium occurred mainly in the apical compartment of intestinal cells. Activation of TLR4 by ligands in combination with cathelicidin promoted CXCL8 chemokine secretion and epithelial antimicrobial defenses against Escherichia coli. We concluded that cathelicidin selectively modulated synthesis of TLR4 and 9 in intestinal epithelium, but only when cells were exposed to virulence factors, mostly from apical surfaces. Enhanced TLR4 expression promoted by cathelicidin in intestinal epithelium may be crucial for controlling enteric infectious diseases.